Analysis the Implementation of STEAM Approach on Creative Thinking Ability in Science Learning - Elsiaulavita Gracia; Sabar Nurohman; Insih Wilujeng (Postgraduate, University of Mataram, 2024)
This study aims to analyze the impact of applying the STEAM (Science, Technology, Engineering, Arts, Mathematics) approach in science education on students' creative thinking skills. The STEAM approach offers an integration of various disciplines, creating a holistic and interactive learning environment that has proven effective in enhancing creative thinking skills. The method used is content analysis with a qualitative descriptive approach, through a literature review of national and international journals. The results from 11 journals show that the application of STEAM in science education has a significant effect on improving students' creative thinking skills. STEAM-based learning encourages students to be more active in exploring ideas, designing innovative solutions, and connecting scientific concepts to real life. The discussion reveals that traditional teaching methods, which tend to be passive, contribute to the low level of students' creative thinking skills, while STEAM offers a more contextual approach involving hands-on experiences. In conclusion, the STEAM approach has been proven effective in improving the quality of science education and developing students' creative thinking skills, thus preparing them to face the challenges of the 21st century.